2022
DOI: 10.21037/jtd-22-569
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis, clustering, and immune cell infiltration analysis of m6A-related genes in patients with acute myocardial infarction—a bioinformatics analysis

Abstract: Background: Accurate myocardial infarction (AMI) is one of the leading causes of mortality worldwide.N6-methyladenosine (m6A) modification plays an important role in the development of cardiac remodeling and the cardiomyocyte contractile function. The aim of this study is to analyze the m6A-related molecular biological mechanisms of AMI in terms of accurate diagnosis and prognosis. Methods:The platform data and probe data of the GSE66360 data set were downloaded. The differential analysis was conducted by comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Both the expression of genes related to m6A as well as the infiltration of immune cells were distinctly diverse between the two subtypes. It is important to note that the m6A-related genes were, on average, expressed at a higher level in Type A AMI compared to Type B AMI [ 35 ]. Additionally, immune cell infiltration was more common in Type A AMI.…”
Section: Discussionmentioning
confidence: 99%
“…Both the expression of genes related to m6A as well as the infiltration of immune cells were distinctly diverse between the two subtypes. It is important to note that the m6A-related genes were, on average, expressed at a higher level in Type A AMI compared to Type B AMI [ 35 ]. Additionally, immune cell infiltration was more common in Type A AMI.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, GSE66360 microarray including 49 AMI and 50 control samples were obtained from the Gene Expression Omnibus (GEO) database (https://www.ncbi.nlm.nih.gov/geo/) and used as a validation set. In addition, 27 M6A methylation regulators (MMRs) containing 10 writers (METTL3, METTL14, METTL16, WTAP, VIRMA, ZC3H13, RBM15, RBM15B, CBLL1, and KIA1499), 2 erasers (ALKBH5 and FTO), and 15 readers (YTHDC1, YTHDC2, YTHDF1, YTHDF2, YTHDF3, HNRNPC, FMR1, LRPPRC, HNRNPA2B1, IGFBP1, IGFBP2, IGFBP3, RBMX, ELAVL1, and IGF2BP1) were obtained from published articles [14,16]. 149 Ferroptosis related genes (FRGs) were sourced from the published article [17].…”
Section: Data Collectionmentioning
confidence: 99%
“…N6-methyladenosine (m6A) modi cation is one of the common epigenetic modi cations, accounting for more than 80% of all RNA modi cations [13]. Previous studies have found that m6A methylation is widely involved in the development of various types of cardiovascular diseases [14] and may provide a reference to explore the occurrence of slow ow/no re ow. In addition, Ferroptosis is one of the forms of programmed cell death that acts differently from apoptosis, necrosis, and autophagy, with the main mechanism being that unsaturated fatty acids from the cell membrane are catalyzed in the presence of divalent iron or ester oxygenases, which activate lipid peroxidation and induce cell death.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, compared with other methods, the random forest method is more effective in identifying key genes significantly associated with disease. [ 17 ]. Recently, as a widely applied analytical method, CIBERSORT has often been used to study the immune cell infiltration pattern in diseases based on RNA sequencing or microarray data and to evaluate the infiltrated proportion of 22 immune cells in each sample [ 18 ].…”
Section: Introductionmentioning
confidence: 99%